Design study of a pyrolysis plant compressor with heavy wall erosion from metal particle impact - Omri, Riadh; Semel, Matthias; Delgado, Antonio; Rußwurm, Hans (Proceedings of the ASME 2017 Fluids Engineering Division Summer Meeting. Volume 1A, Symposia: Keynotes; Advances in Numerical Modeling for Turbomachinery Flow Optimization; Fluid Machinery; Industrial and Environmental Applications of Fluid Mechanics, 2017)
In a pyrolysis plant, a mounted centrifugal compressor takes heavy damage because of erosion originating from metal particle mixed with the inlet air flow impacting its blades and volute walls. In a first step, the original impeller design as well as other centrifugal compressor designs are studied to identify the design parameters which influence the erosion distribution, shape and magnitude. It has been concluded that the first impact plays an important role in defining the particles trajectories and the erosion on the walls. A novel impeller design method based on particle trajectories after a controlled first impact is introduced. The new setup is simulated via CFD coupled with Finnie erosion model to assess the damage. This design is improved in a further step. Adequate simulation setups such as interfaces, boundary conditions and particle coupling methods with carrier fluid are introduced. This study focuses on predicting the particle trajectory within the impeller to reduce the impacts on blade walls and thus reducing the erosion rate. For all designs, the analysis is conducted in the same stage operating point, this point is defined at a predefined volume flow VF [kg/m3] and total-to-static pressure Δp[Pa] as is recommended for the pyrolysis facility including the compressor. Simulations are conducted in a steady state with compressible air at high static temperature going to 530°C. For CFD calculations the software in use is CFX of the ANSYS Group. All mesh used is structured and produced by TurboGrid for the blade rows and with Icem for inlet, outlet and volute. The final compressor design contain the design recommendation for hub form and outlet flow angle.